coastDat-2 TRIM-NP-2d Tide-Surge North Sea ... - Gaslikova, Lidia; Weisse, Ralf (World Data Center for Climate (WDCC) at DKRZ, 2013)
Project: coastDat-2 - CoastDat-2 (http://www.coastdat.de/about_us/index.php) comprises a compilation of coastal analyses (that is hindcasts and reconstructions) and scenarios for the future obtained from numerical models. The atmospheric part of the dataset is simulatated using the COSMO-CLM (http://www.clm-community.eu). The objective is to provide a consistent meteo-marine data set. Summary: This is a hydrodynamic hindcast for the North Sea and the Northeast Atlantic over the period 1948-2015. The simulation has been performed with the hydrodynamic model TRIM-NP V2.1.22 in barotropic 2D mode. Water level and current component fields are stored hourly. The model is set up on an equidistant Cartesian grid cascade with the center near Helgoland (7.88 E, 54.18 N). The coarsest grid with 12.8 km resolution covers the area from 20 W to 30 E and from 42 N to 65 N. Further 3 nested grids better resolve the North Sea (with 6.4km), southern North Sea (with 3.2km) and the German Bight (with 1.6km). Model data from ...